Wing morphology variations in Culicoides circumscriptus from France - Hadj-Henni, Leila; Djerada, Zoubir; Millot, Christine; Cousinat, Mireille; Lehrter, Véronique; Augot, Denis (Frontiers in Veterinary Science, 2023)
The biting midge Culicoides circumscriptus is a European widespread vector of avian malaria throughout the continent and is a possible vector of Akabane virus and Bluetongue virus. This species populates a wide range of environments in contrasting ecological settings often exposed to strong seasonal fluctuations. The main goals of this study were to investigate C. circumscriptus phenotypic variation at three departments in France (Corsica Island, Moselle and Var) and to determine if its phenotypes vary with the environment. Culicoides circumscriptus wing phenotypes were analyzed using a geometric morphometric approach based on anatomical landmarks and outlines of the wing. Dendogram trees based on landmarks and the outlines-2 set (cell m4) showed similar topologies and separated populations of C. circumscriptus. In contrast, another set of outlines-1 (covering the r-m cross vein, M, radiale and arculus) presented a different hierarchical clustering tree. The phenotypic variation observed in C. circumscriptus indicated that these populations are exposed to environmental and ecological pressures. Our results suggest the presence of phenotypic plasticity in this species.